Iron deficiency is related to low functional outcome in patients at early rehabilitation after acute stroke. Issue 2 (14th February 2022) - Doehner, Wolfram; Scherbakov, Nadja; Schellenberg, Tim; Jankowska, Ewa A.; Scheitz, Jan F.; von Haehling, Stephan; Joebges, Michael
Abstract: Background: Iron deficiency (ID) is a common co‐morbidity in patients with cardiovascular disease and contributes to impaired functional capacity. The relevance of ID in patients in recovery after acute stroke is not known. We assessed the prevalence of ID and anaemia in relation to functional capacity and to recovery during early rehabilitation after stroke. Methods: This observational study enrolled consecutively 746 patients with ischaemic or haemorrhagic stroke at in‐patient early rehabilitation (age 68 ± 13 years, female 47%, ischaemic stroke 87%). Functional capacity was assessed before and after rehabilitation using Barthel index (reha‐BI), motricity index (MI), trunk control test (TCT), and functional ambulatory category (FAC). ID was defined as ferritin <100 μg/L or as transferrin saturation (TSAT) < 20% if ferritin was 100‐ < 300 μg/L or if CrP > 5 mg/L. Anaemia was defined as Hb < 12 g/dL (women) and <13 g/dL (men). Results: The prevalence of ID and anaemia before rehabilitation were 45% and 46%, respectively, and remained high at discharge (after 27 ± 17 days) at 40% and 48%, respectively. Patients with ID had lower functional capacity compared with patients without ID (reha‐BI 20 [±86] vs. 40 [±80], MI 64 [±66] vs. 77 [±41], TCT 61 [±76] vs. 100 [±39], FAC 1 [±4] vs. 4 [±4]; median [IQR], all P < 0.001). ID was related to inflammation (OR 2.68 [95% CI 1.98–3.63], P < 0.001), female sex (OR 2.13 [95% CI 1.59–2.85], P < 0.001), haemorrhagic stroke (OR 1.70 [95% CI 1.11–2.61], P = 0.015), initial treatment on stroke unit (OR 3.59 [95% CI 1.08–11.89], P < 0.001), and anaemia (OR 2.94 [95% CI 2.18–3.96], P < 0.001), while age, BMI, and renal function were not related to ID. In adjusted analysis, ID was associated with low functional capacity in all functional scores: reha‐BI (OR 1.66 [95% CI 1.08–2.54], P = 0.02), motricity index (OR 1.94 [95% CI 1.36–2.76], P < 0.001), trunk control test (OR 2.34 [95% CI] 1.64–3.32, P < 0.001) and functional ambulatory category (OR 1.77 [95% CI 1.2–2.63], P < 0.02). Functional capacity improved during rehabilitation regardless of presence of ID, but functional outcome remained significantly lower in patients with ID at the end of rehabilitation (rehab BI and MI, both P < 0.001). Conclusions: Iron deficiency and anaemia are common and persistent findings in patients after acute stroke. ID and anaemia are independently related to lower functional capacity after acute stroke and to poor functional outcome after rehabilitation. Regular assessment of iron status may identify patients at risk of low functional recovery.